Analysis of the diagnostic informativity of non-contrast computed tomography markers of intracerebral hemorrhage expansion in assessment of the individual risk of early neurological deterioration in patients with hemorrhagic hemispheric stroke - Кuznietsov, А. А.; Кузнєцов, Антон Анатолійович (Запорізький державний медико-фармацевтичний університет, 2023)
The aim of the study was to evaluate the diagnostic informativity of non-contrast computed tomography (NCCT) markers of intracerebral hemorrhage (ICH) expansion in assessment of the individual risk of early neurological deterioration (END) in patients with hemorrhagic hemispheric stroke (HHS). Materials and methods. A prospective, cohort study was conducted involving 333 patients in the acute period of hypertensive spontaneous supratentorial ICH on the background of conservative therapy. The level of neurological deficit was assessed using the Full Outline of Unresponsiveness (FOUR) coma scale and the National Institute of Health Stroke Scale (NIHSS). The computed tomography of the brain was used to verify the ICH volume, the midline shift (MS), the secondary intraventricular hemorrhage volume (IVHV) and NCCT markers of intracerebral hemorrhage expansion. As a combined clinical endpoint, END was considered (decrease of the FOUR scale score ≥2 or/and increase of the NIHSS score ≥4 or/and lethal outcome within 48 hours of hospitalization). Results. Early neurological deterioration was registered in 112 patients. On the basis of a comparative analysis, it was established that the specific weight of END was significantly higher in subcohorts of patients with individual NCCT markers of intracerebral hemorrhage expansion, than it was in subcohorts of patients without corresponding NCCT signs (p ˂ 0.0001). It was established that the following NCCT markers of ICH expansion are the most sensitive predictors of END: hypodensity, swirl sign and irregular shape (sensitivity >90.0 %). The most specific NCCT markers were island sign, black hole sign, blend sign, satellite sign and heterogeneous density (specificity >87.0 %). In accordance with the multiple logistic regression analysis, hypodensity (OR (95 % CI) = 13.56 (4.54–40.49), p < 0.0001) and island sign (OR (95 % CI) = 5.94 (2.05–17.16), p = 0.0010) are independently associated with the risk of END. A highly sensitive multi-prediction logistic regression model was elaborated in order to predict END in patients with HHS which takes into account the most informative NCCT markers of ICH expansion (hypodensity, island sign) and quantitative neuroimaging indicators (MS, IVHV) (AUC ± SE (95 % CI) = 0.92 ± 0.02 (0.89–0.95), р ˂ 0.0001). Мета роботи – оцінити інформативність неконтрастних комп’ютерно-томографічних (НККТ) маркерів прогресування внутрішньомозкового крововиливу (ВМК) у визначенні індивідуального ризику раннього клініко-неврологічного погіршення (РКНП) у хворих на геморагічний півкульовий інсульт (ГПІ). Матеріали та методи. Здійснили проспективне, когортне дослідження із залученням 333 пацієнтів у гострому періоді гіпертензивного спонтанного супратенторіального ВМК на тлі консервативної терапії. Рівень неврологічного дефіциту оцінювали за шкалою коми Full Outline of Unresponsiveness (FOUR) та National Institute of Health Stroke Scale (NIHSS). За даними комп’ютерної томографії головного мозку визначили об’єм ВМК, латеральну дислокацію (ЛД) серединних структур мозку, об’єм вторинного внутрішньошлуночкового крововиливу (ОВВШК) та НККТ-маркери прогресування ВМК. Як комбіновану кінцеву клінічну точку визначили РКНП (зменшення сумарного бала за шкалою коми FOUR ≥2 та/або збільшення сумарного бала за NIHSS ≥4, та/або летальний наслідок протягом 48 годин після госпіталізації). Результати. Раннє клініко-неврологічне погіршення зареєстровано у 112 пацієнтів. У результаті порівняльного аналізу встановили: в субкогортах пацієнтів з окремими НККТ-маркерами прогресування ВМК питома вага РКНП достовірно вища, ніж у субкогортах пацієнтів без таких (p ˂ 0,0001). Найчутливіші предиктори РКНП – гіподенсивність, ознака «завихрення» та неправильна форма осередку ураження (чутливість >90,0 %), а найбільш специфічні – ознаки «острівця», «чорної діри», «змішування», «супутника» та гетерогенна щільність осередку ураження (специфічність >87,0 %). За даними множинного логістичного регресійного аналізу, з ризиком РКНП незалежно асоційовані гіподенсивність (ВШ (95 % ДІ) = 13,56 (4,54–40,49), р < 0,0001) та ознака «острівця» (ВШ (95 % ДІ) = 5,94 (2,05–17,16), р = 0,0010). Побудовано високочутливу мультипредикторну логістичну регресійну модель для прогнозування РКНП у хворих на ГПІ, що враховує найінформативніші НККТ-маркери ВМК (гіподенсивність, ознака «острівця») та кількісні нейровізуалізаційні показники (ЛД, ОВВШК) (AUC ± SE (95 % CI) = 0,92 ± 0,02 (0,89–0,95), р ˂ 0,0001).
Аналіз діагностичної інформативності неконтрастних комп’ютерно-томографічних маркерів прогресування внутрішньомозкового крововиливу у визначенні індивідуального ризику раннього клініко-неврологічного погіршення у хворих на геморагічний півкульовий інсульт
ORCID ID: 0000-0002-6118-9682
Keywords: cerebral hemorrhage; x-ray tomography; prognosis; внутрішньомозковий крововилив; рентгенівська томографія; прогноз